Conflictividad social, Educación y Esfera Pública - Mella Polanco , Marcelo (Re-presentaciones: Periodismo, comunicación y sociedad, 2006)
This article analyzes some factors that influence the educational policy and allow explaining the character of the social conflict related to the topic of education quality during the first year of Bachelet's administration. The study deals with problems such us: what is the incidence of the decision processes design in the contents of the policies during Concertación's governments? and, on the other hand, what does the specific conflict in educational matters in our country consist in? The analysis starts with a comment about the general conditions for the implementation of a public policy which can generate governability and political development in the context of the transition and democractic consolidation processes. In the second place, a set of factors that determines the effectiviness of the educational policy -such us: the density of the public sphere, the efficiency of the participation devices and the modus operandi in the elaboration of decisions and policies- will be analyzed. Finally, we try to put these dimensions in the perspective of deep cultural transformations that have allowed the restoration in Chile of the constructive and conflictive dimension of politics.
Keywords: Educational policies; public sphere; participation; policy making; social conflict